Strategi Pemerintah Desa Dalam Meningkatkan Partisipasi Perempuan dalam Proses Musyawarah Perencanaan Pembangunan Infrastruktur Desa di Desa Sagulubbek, Kabupaten Mentawai 2019 - Agustina (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2021)
This study will explain the participation of women in a village infrastructure development planning consultation (musrembang) in Sagulubbek Village, Southwest Siberut District, Mentawai Islands Regency. The method used in this study is a qualitative method, with data collection techniques through virtual in-depth interviews and literature studies. Women's participation is involvement in a political activity, organization, or about musrembang which involves the community, especially women, where there needs to be an increase involvement in village infrastructure musrembang. The results of this study indicate that women do not participate in development planning activities, due to lack of knowledge, experience and understanding in such a deliberation so that women do not participate. In addition, there is minimal education, such as non-formal education from the village government, as well as socialization about the infrastructure development planning process itself. In addition, in participating in the infrastructure musrembang, women are less likely to give their aspirations and opinions in the infrastructure musrembang process. In this case, there is a village government strategy, such as giving authority to each hamlet head to submit information and socialization regarding the village infrastructure development consultation that has been carried out in the infrastructure development development plan of the Sagulubbek village. In addition, the BPD formed a Special Community Empowerment Institute organization for women to participate in illiterate literacy activities, apart from these activities, women also participated in vegetable planting activities as well as cultivating and producing coconut oil for sale.